2. VARIASI GENETIK TANAMAN TOMAT DARI BEBERAPA TEMPAT DI SULAWESI UTARA BERDASARKAN GEN MATK - Lawodi, Eirene Natalia (PHARMACON, 2013)
Identification and preservation of genetic diversity of a population is important inconservation. This study aims to determine the MATK gene variation among tomato plantsfrom several places in Sulawesi and compare it with the closest relatives in GenBank, as wellas create a phylogenetic tree. PCR technique was used to amplify matK gene with universalprimers. â€˜Kinkyâ€™ and â€œAppleâ€ tomatoes were obtained from Minahasa regency of NorthSulawesi province. Both have an identical sequence of partial matK gene. â€œCherryâ€ tomatoobtained from North Minahasa regency of North Sulawesi province has a sequence of partialmatK gene which is identical with â€œcherryâ€ tomatoes obtained from the district of Poso inCentral Sulawesi province. This study implies that both â€œcherryâ€ tomatoes are the ancestor ofboth â€œkinkyâ€ and â€œappleâ€ tomatoes.Key words : Genetic diversity, matK gene, Lycopersicon esculentum, phylogenetic tree